The power of process : the value of due process in Security Council sanctions decision-making - Hovell, Devika, 1975- (Oxford : Oxford University Press, 2016)
Examining the legal principles behind UN Security Council sanctions, Devika Hovell questions whether due process is afforded to sanctioned individuals in the context of the politics and crises that form the heart of the council's decision-making.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 10, 2016).
Keywords: Sanctions (International law) -- Decision making; Due process of law; United Nations. -- Security Council; Law; International law